A construção de uma imagem do caipira: cenas de enunciação e ethos discursivo em causos de Cornélio Pires - Castanho, Eli Gomes (2009)
This dissertation examines the ethos construction of the caipira through the discursive genre tale-story. The corpus of this work is composed by three tales-stories from the book As estrambóticas aventuras de Joaquim Bentinho, o queima-campo (1924), of Cornélio Pires, writer and story-teller from Tietê-SP, who lived in the beginning of twenty century. Our general objective was to examine the scenes of the enunciation and the construction of ethos of the caipira . Our specifics objectives were: to verify the construction of global and generics scenes, characterizers of a type of discourse and genre, respectively; to describe scenographies constructed by the stories-tales; and, through this analytic movement, to observe how is created an image of the caipira , in those scenographies. The caipira s images were historically reconstructed by different medium means. These constants reconstructions brought, in its discourses, different representations of the rural man, since the lazy and alienated man about the economic world, until the bucolic man who lives in peace with the nature and far way the urbans values. Then, it was interesting to us, to notice how the caipira s image was created in that discursive genre. The theorist base of our analysis was upon D. Maingueneau s (2005, 2006c, 2008) perspective. We chose to work with his Global Semantic plans: scenes of the enunciation, ethos and language code. We apprehended in the tale-story as belongs to the literary camp, trough the construction of a global scene that legitimates its; by the generic scene, we understood the story-tale as a discoursive genre; and, according to the scenographics analyses of the three tales-stories, we realized the creation of a relaxing and interaction moment among the planters, in the cold night, in the farm, time to rest after a hard day and enter in other places created by the utterance. After that, we have studied the utterance of the story-tales, we proceeded the study of the caipira s ethos construction kind, in the three texts chosen, that they have as theme: public health, technology and scientific progress and politic. We understood that the construction of the ethos is made by the opposition between the man of the city and the discourses that present the caipira like an antihero. The image constructed presents a countryman characterized by: the resistant and the immunity in the presence of the adversity resultant of the abandonanment of the politics public health; by a particular knowledge that is not less important than the city habitant; and a politic posture. The faces constructed are also confirmed by mechanism of the caipira variant spelling, configuring an own language code. We considered, finally, that the tales-stories draw a countryman ethos that exchanges the antihero for the hero, not accepting, by the humor, a negative and polemic stereotype, since that time until nowadays